TOWARDS IDENTIFYING ASPECTS OF SOFTWARE QUALITY - Dr. Latika Kharb (International Journal of Research Science and Management, 2015)
Software projects are notorious for going past their deadline, going over budget, or both and the problem lies in the estimation of the amount of effort required for the development of a project. Reliability in software is produced by controlling its quality within budget. In early days of computing, software costs constituted a small percentage of overall computer- based system costs but today; software is the most expensive element of virtually all computer based systems. In this paper, we have discussed about the concept of software quality, the various group of people involved and their roles and various aspects of software quality. We have tried to identify the fact that understanding the reality and importance of software quality is the need of hour as the low-quality software just isn’t acceptable in present and/or future time span.